2021
DOI: 10.1007/978-3-030-85969-5_51
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Peatland Management with IoT and Data Analytics

Abstract: Peatland is important to rural communities' livelihood due to its potential for aquaculture and agriculture. Nonetheless, human activities such as slash-and-burn can greatly increase forest fire risk, which can release a great amount of greenhouse gases and carbon dioxide into the atmosphere. To sustainably manage and restore peatlands, the Internet of Things (IoT) system can incorporate with Cyber-Physical System (CPS) for peatland management. In this study, an IoT system is deployed in the peatland to monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This means that our IoT system can continuously monitor and display weather parameters such as rainfall, temperature, and humidity, as well as GWL data from the ground sensor Figure 4 depicts the integration of groundwater level (GWL) into the Fire Weather Index (FWI) system. Previous studies have confirmed the viability of using GWL in place of temperature and rainfall to compute the Drought Code (DC) in the FWI system [28]. Precisely, the Duff Moisture Code (DMC) is calculated using GWL and relative humidity, as opposed to temperature, rainfall, and relative humidity in the original Canadian FWI system (refer to Figure 3).…”
Section: Fire Weather Index (Fwi) Systemmentioning
confidence: 87%
See 1 more Smart Citation
“…This means that our IoT system can continuously monitor and display weather parameters such as rainfall, temperature, and humidity, as well as GWL data from the ground sensor Figure 4 depicts the integration of groundwater level (GWL) into the Fire Weather Index (FWI) system. Previous studies have confirmed the viability of using GWL in place of temperature and rainfall to compute the Drought Code (DC) in the FWI system [28]. Precisely, the Duff Moisture Code (DMC) is calculated using GWL and relative humidity, as opposed to temperature, rainfall, and relative humidity in the original Canadian FWI system (refer to Figure 3).…”
Section: Fire Weather Index (Fwi) Systemmentioning
confidence: 87%
“…Integrating IoT technology into the study of peatlands holds great promise for advancing our understanding of these ecosystems and mitigating the risk of environmental disasters caused by forest fires. Moreover, the system has been used, and many research results based on the IoT system have been published [27][28][29]. To facilitate the smooth flow of groundwater within the pipeline, a small hole is incorporated while ensuring that the gap is not too large to prevent the piezometer from being obstructed by soil and stones.…”
Section: Iot System For Peatland Forest Managementmentioning
confidence: 99%
“…Moreover, it was put into use on 17 January 2020. More information based on the IoT system has been described in detail in our team's previous publication [19][20][21]. The histogram of the data used in this paper is shown in Figure 2.…”
Section: Data Preparationmentioning
confidence: 99%